Deeply reduced empty Keggin clusters [MoIVxMVI12−xO40−xpyx] (x = 3, 6; M = Mo, W; py = pyridine): synthesis, structures, and Lewis field catalysis. Issue 24 (4th November 2021) - Ren, Cuiming; Lu, Zhihao; Luo, Benlong; Yi, Xiaofeng; Lin, Lifang; Xu, Li
Abstract : First Mo IV 3 -Keggin anions [Mo IV x M VI 12− x O40− x py x ] 8−  (M = Mo, W; x = 3, 6) display unprecedented empty Keggin structure caused by the weak u3 -O coordinating capability of the [Mo IV 3 O4 ] triads and LCF-dependent hydrogen transfer catalysis. Abstract : In this research, we present the first examples of MoIV3–W VI hybrid polyoxometalates (MoIV3-POMs) with empty Keggin structures: α-[MoIV3Mo VI WVI8O31 (OH)6 py3 ]·2Hpy·4H2 O (1 ·2Hpy·4H2 O), γ-[MoIV6WVI6O28 (OH)6 py6 ]·2[H2 N(CH3 )2 ]·6.5H2 O (2 ·2[H2 N(CH3 )2 ]·6.5H2 O), γ-[MoIV6WVI6O29 (OH)5 py6 Na(H2 O)5 ]·2[NH2 (CH3 )2 ]·2H2 O (3 ·2[NH2 (CH3 )2 ]·2H2 O) and γ-[{MoIV6Mo VI WVI5O28 (OH)6 py6 }2 Znpy4 ]·2Hpy·8H2 O (4 ·2Hpy·8H2 O). They were prepared through the solvothermal partial oxidation of a mixture of triangular bioxo-capped hexacarboxylate clusters [MoIV x WIV3− x O2 (O2 CCH3 )6 L3 ] q ( x = 0–3, L = H2 O, q = 2+; L = CH3 CO2 −, q = −1), providing a feasible route to the designed synthesis of mixed MoIV3–W POMs. The much lower yield and poor repeatability of 1 compared to those of 2, 3, and 4 are ascribed to the fact that the triangularly Mo IV –Mo IV bonded MoIV3 Lewis acid cluster unit of the former results from the breakage of M IV –W IV bonds (M = Mo, W) and recombination of Mo IV in the Na[Mo IV WIV2O2 (O2 CCH3 )9 ] precursor because of the extremely easy oxidation of W IV to W VI as compared to Mo IV . 2, 3, and 4 exhibit highly LCF-dependent (LCF = Lewis catalysis field) hydrogen transfer catalysis performance in the hydrazine reduction of nitrobenzene to aniline.